2022
DOI: 10.3390/app12094237
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Destructive Technique for Cultural Heritage: Depth Profiling and Elemental Analysis Underneath the Surface with Negative Muons

Abstract: Scientists, curators, historians and archaeologists are always looking for new techniques for the study of archaeological artefacts, especially if they are non-destructive. With most non-destructive investigations, it is challenging to measure beneath the surface. Among the vast board of techniques used for cultural heritage studies, it is difficult to find one able to give information about the bulk and the compositional variations, along with the depth. In addition, most other techniques have self-absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Beams coming from pions decaying in flight are called “decay muons”, allowing for higher and lower momenta and also negative muons. Decay muons can be used in pressure cells, in situations where a negative muon has a clearer interaction with the sample, or to use the X-rays emitted by nuclear capture of negative muons to determine the elements the sample contains, this has particular advantages for studies of cultural heritage objects . All of these techniques work with bulk samples but beams of positive muons can also be moderated to far lower energies, “slow muons” with keV rather than MeV energies, which are used to study thin film materials with thicknesses in the range 10–200 nm …”
Section: Will Neutron Scattering and Muon Spectroscopy Still Be Neede...mentioning
confidence: 99%
“…Beams coming from pions decaying in flight are called “decay muons”, allowing for higher and lower momenta and also negative muons. Decay muons can be used in pressure cells, in situations where a negative muon has a clearer interaction with the sample, or to use the X-rays emitted by nuclear capture of negative muons to determine the elements the sample contains, this has particular advantages for studies of cultural heritage objects . All of these techniques work with bulk samples but beams of positive muons can also be moderated to far lower energies, “slow muons” with keV rather than MeV energies, which are used to study thin film materials with thicknesses in the range 10–200 nm …”
Section: Will Neutron Scattering and Muon Spectroscopy Still Be Neede...mentioning
confidence: 99%
“…This technique is called muonic atom X-ray emission spectroscopy (μ-XES) and has two main advantages over its X-ray counterpart due to the intrinsic properties of the muon: it is non destructive, and the emitted signal is much more energetic making it possible to detect light elements such as lithium. 147 So far, this technique has been mainly applied to cultural heritage studies due to the non-destructiveness of the technique, 145 however, Umegaki et al used μ-XES to detect metallic lithium deposited on a graphite anode. 146 They found that the intensity of muonic X-rays from metallic lithium was about 50 times higher than that of lithium ions, which allowed them to clearly distinguish between both.…”
Section: Muon Spectroscopymentioning
confidence: 99%
“…The process, after initial muon-induced Auger emission, becomes radiative, with the emission of high-energy X-rays (an extensive description of muon capture and muonic atoms can be found here [13]). With a particular interest in Cultural Heritage studies, the technique has many fields of applications, from the characterization of lithium batteries to meteorites to material engineering [14][15][16][17][18][19][20][21][22]. Given its novelty, the technique has room for improvement, especially as it is now performed at the ISIS facility in terms of detector, electronics and data interpretation.…”
Section: Introductionmentioning
confidence: 99%